De-feminization and (Dis)empowerment of Women Workers in Garment Factories. Issue 1 (June 2018) - Prasad, Archana
Economic globalization led to the restructuring of global production process. It has led to a decline in the participation of women in the formal sector and the deterioration in their conditions as workers. This article studies the export processing zones (EPZs) of India. By using qualitative data collected through ethnographic study of the women workers in the garment factories in Delhi, this article shows how the lack of labour standards or unions in these zones have made women workers more casualized, informal and vulnerable. They suffer from discrimination, sexual harassment and are denied the basic right to work.